(untitled) (Persona y Derecho, 2019)
The article revisits and seeks to clarify and provide with new perspectives the debate between the theoretical approaches of four authors – Michel Villey, Brian Tierney, John Finnis and Javier Hervada – in their accounts of the contemporary formulation of the concept of “ius”. Although all authors analyzed in the paper share common thomistic roots in their respective argumentations on the essential meaning and content of the concept of “right”, they still differ in their accounts with regard to the understanding of Aquinas’s classical juridical realism, the relation between “law” and “right” and the role of subjective rights in history and in today’s juridical discourse. The paper seeks to highlight how such comparative perspective reveals not only the contrasts in the theoretical accounts of these authors with regard to the structural “locus” of the focal point of juridicity, but also renders manifest certain perspectives of integration of each approach with contributions achieved by the other interlocutors of the debate.